Characterisation of Sonosensitive Nano-Sized Formulations - Hiltl, Pia-Theresa; George, Benedikt; Fink, Michael; Rupitsch, Stefan; Ermert, Helmut; Lee, Geoffrey (3rd European Conference on Pharmaceutics, 2019)

Characterization of Acoustic Properties of Poly-(L)-lactic Acid Nanoparticles in terms of Inertial Cavitation - Hiltl, Pia-Theresa; Fink, Michael; Hofmann, Astrid; Ermert, Helmut; Rupitsch, Stefan; Lee, Geoffrey (Biomedizinische Tagung 2018, 2018)

Determination of the Cavitation Pressure Threshold in Focused Ultrasound Wave Fields applied to Sonosensitive, Biocompatible Nanoparticles for Drug Delivery Applications - George, Benedikt; Lehner, Markus; Fink, Michael; Rupitsch, Stefan; Hiltl, Pia-Theresa; Savsek, Ula; Lee, Geoffrey; Ermert, Helmut (Current Directions in Biomedical Engineering 2020, 2020)

Development of Sonosensitive Poly-(L)-lactic Acid Nanoparticles - Hiltl, Pia-Theresa; Fink, Michael; Rupitsch, Stefan; Lee, Geoffrey; Ermert, Helmut (Current Directions in Biomedical Engineering 2017, 2017)

Inertial cavitation of lyophilized and rehydrated nanoparticles of poly(L-lactic acid) at 835 kHz and 1.8 MPa ultrasound - Hiltl, Pia-Theresa; Grebner, Alexander; Fink, Michael; Rupitsch, Stefan; Ermert, Helmut; Lee, Geoffrey (Scientific Reports, 2019)
Nanoparticles of poly-L-lactic acid dispersed in water and of approximately 120 nm diameter were prepared by a nanoprecipitation method followed by lyophilization together with trehalose. After rehydration, the nanodispersion was exposed to ultrasound at 835 kHz frequency and 1.8 MPa peak negative sound pressure. Substantial levels of broadband noise were surprisingly detected which are attributed to the occurance of inertial cavitation of bubbles present in the dispersion. Inertial cavitation encompasses the formation and growth of gas cavities in the rarefaction pressure cycle which collapse in the compression cycle because of the inwardly-acting inertia of the contracting gas-liquid interface. The intensity of this inertial cavitation over 600 s was similar to that produced by Optison microbubbles used as contrast agents for diagnostic ultrasound. Non-lyophilized nanodispersions produced negligible broadband noise showing that lyophilization and rehydration are requirements for broadband activity of the nanoparticles. Photon correlation spectroscopy indicates that the nanoparticles are not highly aggregated in the nanodispersion and this is supported by scanning (SEM) and transmission (TEM) electron micrographs. TEM visualized non-spherical nanoparticles with a degree of irregular, non-smooth surfaces. Although the presence of small aggregates with inter-particulate gas pockets cannot be ruled out, the inertial cavitation activity can be explained by incomplete wetting of the nanoparticle surface during rehydration of the lyophilizate. Nano-scale gas pockets may be trapped in the surface roughness of the nanoparticles and may be released and coalesce to the size required to nucleate inertial cavitation on insonation at 835 kHz/1.8 MPa.
CRIS-Team Scopus Importer:2019-08-30

Investigation of Inertial Cavitation Stimulation by Focused Ultrasound on Sonosensitive Nanoparticles for Drug Delivery Applications - George, Benedikt; Fink, Michael; Rupitsch, Stefan; Hiltl, Pia-Theresa; Lee, Geoffrey; Ermert, Helmut (Proceedings IEEE IUS 2019, 2019)

Investigation of the Inertial Cavitation Activity of Sonosensitive and Biocompatible Nanoparticles for Drug Delivery Applications Employing High Intensity Focused Ultrasound - George, Benedikt; Rupitsch, Stefan; Fink, Michael; Ermert, Helmut; Hiltl, Pia-Theresa; Lee, Geoffrey (Current Directions in Biomedical Engineering 2019, 2019)

Measurement of the Cavitation Activity of Sonosensitive Nanoparticles used for Local Chemotherapy - George, Benedikt; Fink, Michael; Plock, Maren; Hiltl, Pia-Theresa; Ermert, Helmut; Lee, Geoffrey; Rupitsch, Stefan (6. Tagung Innovation Messtechnik, 2019)
Keywords: Messtechnik; Sensoren; Messelektronik